Relationship between the morphology of the maxillary central incisor and horizontal and vertical measurements of the face - Paranhos, Luizrenato; Furtado, Giselacrippa; Furtado, Alvaro; El Haje, Ossamabu; Butignon, Luiseduardo; Pesqueira, Aldiéris Alves [UNESP] (Wolters Kluwer, 2014)
Purpose: In order to assist in the selection of artificial teeth for complete dentures, this study aimed to assess the relationship between horizontal and vertical measurements of the face and the morphology of the maxillary central incisor. Materials and Methods: This was a study of 50 plaster casts and 100 teleradiographs - 50 in lateral norm and 50 in frontal norm, belonging to 50 individuals, Caucasian, with a naturally optimal occlusion, matching at least four of the six keys of Andrews. Images of the upper central incisors were obtained by scanning the plaster casts (three-dimensional) and subjectively classified by three examiners as oval, triangular or quadrangular. Facial measures (vertical and horizontal) were defined by means of teleradiographs. In order to check inter-examiner agreement on the classification of central incisor, the Kappa test was used. To verify whether data had normal distribution, the Kolmogorov-Smirnov test was used ( P > 0.2) was used. One-way analysis of variance was employed to assess the association between variables (P > 0.05). Results: When vertical measurements were compared with the three incisor shapes, there was no statistically significant difference (P > 0.05): Triangular (0.54), oval (0.63) and quadrangular (0.51). Similarly, no difference (P > 0.05) was found for facial width (139.08, 143.37, 141.65), maxillary width (76.68, 78.99, 76.91) and mandibular width (103.47, 105.50, 103.11). Conclusions: The majority of cases showed that horizontal and vertical measurements of the face cannot be used as a reference for determining the morphology of the maxillary central incisor crown. It is relevant to analyze and compare other morphological structures to improve the oral health-related quality of life for the conventional denture wearer.
Keywords: Cephalometry; Face; Form perception; Tooth